1996
DOI: 10.1128/mcb.16.6.2728
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Partially Transforming Polyomavirus Mutants Establish a Role for Phosphatidylinositol 3-Kinase in Activation of pp70 S6 Kinase

Abstract: Infection of mouse fibroblasts by wild-type polyomavirus results in increased phosphorylation) as a target for signal transduction events leading from polyomavirus middle tumor antigen (mT). Two partially transforming virus mutants altered in different mT signalling pathways have been studied to elucidate the pathway leading to S6 phosphorylation. An upstream role for mT-phosphatidylinositol 3-kinase (PI3K) complexes in pp70 S6K activation is implicated by the failure of 315YF, a mutant unable to promote PI3K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 74 publications
(79 reference statements)
3
47
1
1
Order By: Relevance
“…Another kinase associated with growth factor stimulation, p70 S6-kinase , is activated by constitutively active mutants of PKB/Akt, but is not a direct substrate (Burgering and Co er, 1995). p70 S6-kinase activation has also been observed as a consequence of polyomavirus infection (Talmage et al, 1988;Dahl et al, 1996). The involvement of PKB/Akt in growth regulation is further supported by data obtained with an oncogenic form of PKB/Akt expressed as a Gag-PKB/Akt fusion protein by the acute retrovirus AKT8 (Bellacosa et al, 1991).…”
Section: Middle-t Activates Pkb/aktmentioning
confidence: 65%
See 1 more Smart Citation
“…Another kinase associated with growth factor stimulation, p70 S6-kinase , is activated by constitutively active mutants of PKB/Akt, but is not a direct substrate (Burgering and Co er, 1995). p70 S6-kinase activation has also been observed as a consequence of polyomavirus infection (Talmage et al, 1988;Dahl et al, 1996). The involvement of PKB/Akt in growth regulation is further supported by data obtained with an oncogenic form of PKB/Akt expressed as a Gag-PKB/Akt fusion protein by the acute retrovirus AKT8 (Bellacosa et al, 1991).…”
Section: Middle-t Activates Pkb/aktmentioning
confidence: 65%
“…It has also been shown that PI 3-kinase is required for full activation of the Ras/MAPK pathway by middle-T as well as for signaling to serum response factor (Urich et al, 1997). Mutants of middle-T still capable of activating PI 3-kinase, but lacking a binding site for SHC, trigger stimulation of p70 S6-kinase (Dahl et al, 1996) or p21 Rac -mediated transcriptional regulation (Urich et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the 248, mutant displays lower levels of the PI(3,4,5)P 3 and PI(3,4)P 2 products when compared to wild type MT cell lines. Activation of PI3K leads to activation of pp70 s6k (an essential kinase for G1 progression) in PDGF stimulated (Chung et al, 1994) and MT-transformed cell lines (Dahl et al, 1996). High pp70 S6k activity observed in wild type and 250 MT mutants but not in 315 MT mutants, can be inhibited by wortmannin (Dahl et al, 1996) suggesting di erences in the downstream signals activated by these two MT mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The use of wortmannin as a potent and speci®c inhibitor of PI3K (Powis et al, 1994) was shown to block both MAPK translocation to the nucleus in MT overexpressing and in serum stimulated cells (Urich et al, 1995) and activation of pp70 s6k in WT and 250phe mutants (Dahl et al, 1996). To test whether inactivation of PI3K by this speci®c inhibitor would alter the AP-1 activity displayed by wild type MT cell line, we performed gel shift assays using lysates from cultures treated with 100 nM wortmannin for di erent periods of time (data not shown).…”
Section: Mt Binding To P13k Is Necessary For Constitutive Ap-1 Activitymentioning
confidence: 99%
See 1 more Smart Citation